2004
DOI: 10.1590/s0100-736x2004000300001
|View full text |Cite
|
Sign up to set email alerts
|

Uso da ciclofosfamida em modelo de imunodepressão experimental em ovinos

Abstract: Ovine Ovine experimental immunosuppression using cyclophosphamide. experimental immunosuppression using cyclophosphamide. experimental immunosuppression using cyclophosphamide. experimental immunosuppression using cyclophosphamide. experimental immunosuppression using cyclophosphamide.] Uso da ciclofosfamida em modelo experimental de imunodepressão experimental em ovinos. Pesquisa Veterinária Brasileira 24(3): 115-119. Curso de Medicina Veterinária, Universidade Paulista, Rua Enjolras Vampré 146, São Paulo, SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
2
1
0
1
Order By: Relevance
“…The immune response role in helminthiasis was also demonstrated by Garcia et al. (12), that demonstrated more severe helminthiasis development when previously induced immunossupression in sheep using cyclophosphamide.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…The immune response role in helminthiasis was also demonstrated by Garcia et al. (12), that demonstrated more severe helminthiasis development when previously induced immunossupression in sheep using cyclophosphamide.…”
Section: Introductionsupporting
confidence: 52%
“…There was also demonstrated that T lymphocytes from T. colbriforms infected sheep (46) and Ostertagia ostertagi infected cattle (47) showed in vitro decrease of the proliferative response to mitogen. Severe helminthiasis was also observed when sheep was submitted to immunosuppression by cyclophosphamide treatment (12).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the global blood count, it was observed that the groups not treated and treated with vehicle had WBC values significantly higher than the CF group. This is in line with what was described by Garcia et al (2004), who stated that this effect is due to CF, which is a potent immunosuppressant that acts on cells with high mitotic activity, inhibiting the humoral and cellular immune response. Despite treating malignant and non-malignant diseases (Hosseinimehr & Karami, 2005), the side effectsmost commonly observed with CF use refers to the effect on the hematopoietic tissue, causing myelodepression (leukopenia, thrombocytopenia, anemia) (Schuurman et al, 2005), a fact confirmed by the World Health Organization (WHO), which points it out as the most commonly reported adverse reactions in patients undergoing chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…A leucopenia encontrada no presente estudo, foi também descrita por Garcia et al (2004) em ovinos no modelo de imunossupressão experimental. Segundo demonstrado por Hellman e Grate (1976) a ciclofosfamida mata grande parte das células precursoras na medula, além de diminuir o potencial eritropoiético das células restantes.…”
Section: Resultsunclassified